2022
DOI: 10.1002/ppul.25979
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory distress syndrome in preterm infants of less than 32 weeks: What difference does giving 100 or 200 mg/kg of exogenous surfactant make?

Abstract: Background: Surfactant dosing and effective delivery could affect continuous positive airways pressure (CPAP)-failure. Nevertheless, information on exogenous surfactant dosing with current administration methods is limited.Objective: To describe the effect of 100 or 200 mg/kg of surfactant as first-line treatment of respiratory distress syndrome in preterm infants of less than 32 weeks gestation.Study Design: A retrospective single-center cohort study comparing two epochs, before and after switching from 100 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Many infants can continue on NIV even when surfactant is required. If poractant alfa is used, need for re-dosing can be minimised by using a larger initial dose of 200 mg/ kg [92]. For other surfactants, such data are not available.…”
Section: Repeated Surfactant Dosingmentioning
confidence: 99%
“…Many infants can continue on NIV even when surfactant is required. If poractant alfa is used, need for re-dosing can be minimised by using a larger initial dose of 200 mg/ kg [92]. For other surfactants, such data are not available.…”
Section: Repeated Surfactant Dosingmentioning
confidence: 99%
“…Still, regarding the dose of surfactant, a recent retrospective study conducted in Italy 19 showed that a higher initial dose of surfactant (200 mg/kg) had an advantage over the lower dose (100 mg/kg), with a lower incidence of BPD or duration of mechanical ventilation. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Intakes were collected daily, with complete records of amount and type of parenteral nutrition (PN) and enteral nutrition (EN). The detailed neonatal intensive care unit (NICU) nutrition protocol and criteria for surfactant administration have already been published 24,28 . Complications of prematurity were defined according to the Vermont Oxford definitions.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed neonatal intensive care unit (NICU) nutrition protocol and criteria for surfactant administration have already been published. 24,28 Complications of prematurity were defined according to the Vermont Oxford definitions. SGA was defined as having a BW below the 10th centile, whereas AGA as a BW between the 10th and 90th centile according to the Italian growth charts.…”
Section: Data Collectionmentioning
confidence: 99%